MISANDRY TOWARDS MEN IN THELMA AND LOUISE MOVIE - Nurhilal, Fadhilah; Mustikawati, Yunitari (Journal of English Literature and Linguistic Studies, 2025)
This research raises the topic of misandry in “Thelma and Louise” movie. This study was made to understand the reasons that play a role as the main reason for the action of misandry. In addition, this study aimed at describing the representation of misandry in Thelma and Louise movie. This research used a qualitative approach through the semiotic theory by Roland Barthes (1964) to find out the reasons also the representation of misandry used denotation and connotation in “Thelma and Louise movie”. The results of this research indicated that there were 4 categories of the reasons behind the act of misandry, including toxic femininity, rape, love scams, and become the object of sexual fantasy. For the representation of misandry,  there were classsified into 5 categories, such as mocking, underestimating, unwelcoming behavior, criminality, and generalizing men. Based on the results, the representation of misandry in “Thelma and Louise” movie concluded as the impact of personal experiences of unpleasant treatment experienced by the main characters.